Discarded cigarette filter-derived hierarchically porous carbon@graphene composites for lithium–sulfur batteries. Issue 8 (7th February 2019) - Xu, Hongbin; Liu, Yang; Bai, Qianyun; Wu, Renbing
Abstract : Trash to treasure: discarded cigarette filters have been utilized to fabricate hierarchical macro–micro–mesoporous carbon@graphene composites, which enable high sulfur loading and confine the dissolution of lithium polysulfides, and thus exhibit an excellent electrochemical performance in Li–S batteries. Abstract : Discarded cigarette filters mainly composed of cellulose acetate (CA) are non-biodegradable and can cause a severe environmental pollution hazard. In an effort to turn waste into wealth, herein, we explore hierarchically porous carbon@graphene composites derived from cigarette filters as efficient cathode hosts for lithium–sulfur (Li–S) batteries. The hierarchical porous structure enables high sulfur loading and confines the dissolution of lithium polysulfides while the strongly coupled graphene provides an electrically conductive network for electrons to transfer within the composites. Accordingly, the cigarette filter-derived porous carbon@graphene-based cathode containing 78 wt% sulfur could achieve a high capacity of 1010 mA h g −1 at 0.2C after 200 cycles and even 722 mA h g −1 at 0.5C over 1000 cycles with only ∼0.04% capacity loss per cycle. The findings may open a new trash-to-treasure avenue for the development of high-performance electrode materials in energy storage devices.